Experimental Study: Children's Perceptions Expressed Through Drawings and Coloring. Issue 4 (August 2022) - Trifunović, Aleksandar; Pešić, Dalibor; Čičević, Svetlana
A large body of literature has addressed processes underlying human perception, with some assertions that children do not perceive space or colors in the same way as adults. Since children express themselves easily and acquire knowledge through graphic symbols, when determining psycho-motor maturity and perceptions of a preschool aged children, observers must evaluate their use of non-verbal graphics. Thus, we used young children's drawings to examine their use of color and spatial perception, as well as to identify differences between children in rural and urban communities. Of 94 participants from rural and urban communities, 46 were kindergarten aged (5.5–6.5 years), and 48 were preschool aged (4.5–5.5 years). Comparing children from urban and rural areas, there were significant differences in their perception of different colors and spatial relations. Motor abilities were significantly different between children of different ages and gender. We argue that the applied assessment methods, such as children's drawings, could be a basis for measuring effective learning and practicing of children's abilities as expressed in the classroom, and that tools may be useful for creating individualized educational plans and programs for developing children's skills through play.